Effect of Supplementation of Organic Acids and Their Combination as an Alternative to Antibiotic Growth Promoter on Performance, Gut Health, Immune Status and Economics of Broiler Production - Ahmed, Asrar; Dhumal, M. V.; Nikam, M. G.; Nandedkar, P. V.; Ingle, V. S. (International Journal of Livestock Research, 2019)
An experiment was conducted on 360 Vencobb400 day old straight run chicks which were weighed and distributed randomly into six treatment groups viz. A, B, C, D, E and F with four replicates of 15 chicks. The treatment group A was served feed without organic acid and BMD. Treatment B had Bacitracin Methylene Disalicylate (BMD).The treatment groups C, D and E were supplemented with sodium citrate, ammonium formate, calcium propionate @ 1g/kg feed, respectively. Treatment F had combination of sodium citrate, ammonium formate and calcium propionate each @ 1 g/kg feed. The body weight, feed consumption and feed conversion ratio were significantly affected (P <0.01) by organic acids and their combination. The pH of crop (P<0.01) and ileum (P<0.05) differed significantly. The serum antibody titre of IBD at 21st day had significant (P<0.01) difference. The net profit per kg was higher in organic acid groups. It is concluded that ammonium formate, sodium citrate, calcium propionate and their combination are beneficial for growth performance, gut health, immune status, profitability and may be used as an alternative to BMD.